Violence against women in couples : Latin America and the Caribbean : a proposal for measuring its incidence and trends - Alméras, Diane...[et al.] (ECLAC SantiagoCL, 2004)
Describes how the problem of violence against women came to be part of the public agenda. Presents a classification and non-exhaustive analysis of the surveys and administrative records used to measure violence against women in recent years, highlighting the main lessons learnt.